Characterization and Inhibition of the Main Protease of Severe Acute Respiratory Syndrome Coronavirus. Issue 2 (25th February 2015) - Kuo, Chih‐Jung; Liang, Po‐Huang; Guo, Rey‐Ting
Abstract The main protease of SARS‐associated coronavirus (SARS‐CoV), also called 3C‐like protease (3CLpro), is vital for the viral replication. It cleaves the replicase polyproteins at 11 sites and is a promising drug target. Several groups of inhibitors have been identified through high‐throughput screening and rational drug design. In addition to the pharmaceutical applications, a mutant 3CLpro (T25G) with an expanded S1′ space has been demonstrated to tolerate larger residues at P1′, facilitating the cleavage behind the recognition sequence. This review summarizes current developments in anti‐SARS agents targeting 3CLpro and the application of the mutant protease as a tag‐cleavage endopeptidase.